BER performance of OFDM system with the effect of error control code - Jamil, Muhammad Sobrun; Abdullah, Aizura; Rahman, Muhammad Towfiqr; Abdullah, Khaizuran; Mohd. Ramli, Huda Adibah; Ismail, Ahmad Fadzil (IEEE, 2014)
Orthogonal Frequency Division Multiplexing (OFDM) is one of the promising modulation techniques suitable for high data rates in a wireless communication system. OFDM is the most effective modulation technique suitable for multipath communication channel and fading environment at reasonable complexity. However, the existence of Error Control Coding (ECC) in OFDM system is necessary for the reliable data transmission. This is due to the capability of ECC which can detect and correct the data received. Two types of ECC performance which are Hamming code and convolutional code are investigated in this paper. The simulation system and parameter are described and the results are discussed.